Primary surgical therapy for locally limited oral tongue cancer - Mantsopoulos, Konstantinos; Psychogios, Georgios; Kuenzel, Julian; Waldfahrer, Frank; Zenk, Johannes; Iro, Heinrich (BioMed Research International, 2014)
The aim of this study was to assess the efficacy of primary surgical treatment in the management of locally limited oral tongue carcinoma.A retrospective evaluation was carried out for all patients treated with primary surgery for pT1-pT2 oral tongue carcinomas at a tertiary referral center between 1980 and 2005. All cases were assessed for disease-specific survival and local control rates in relation to T classification, N classification, infiltration depth of the primary tumor, and decision making on neck management and adjuvant therapy. The cases were additionally evaluated for the incidence of major complications and tracheotomies.263 cases were assessed. The 5-year disease-specific survival rate was 75.2%. Positive neck disease was shown to be a significant negative prognostic factor. The occult metastasis rate was 20.2%.Primary surgical treatment is a very effective modality against T1-T2 oral tongue carcinoma, and a low rate of complications can be anticipated.
EVALuna2:19930